Pojavljanje lesne sove Strix aluco v notranjskih in primorskih kraških jamah - Polak, Slavko (Acrocephalus, 2000)
For his present contribution, the author gathered all the available data of the occurrence of Tawny Owl Strix aluco and its pellets in 15 karst caves of the Notranjska and Primorska regions. The owls were observed in accessible horizontal caves and particularly in vertical pitches hard of access, i.e. at their entrances as well as in their inner parts. The greatest depth at which the owls' traces were found reached 100 m in the Brimšca cave near Kozina, where a nest with eggs was found at the bottom of the entrance pitch. The eggshells and bones of the young found in the caves of Jama v Suhi rebri and Križna jama are also a proof that Tawny Owls occasionally breed in these caves. One of the causes for this phenomenon could very possibly lie, according ro the author, in the lack of tree holes and other suitable nest-sites on the surface. The author also states that the owls are a kind of a food vector for the troglobiontic animals in their poor underground environment. In general, the speleological literature does not include owls, and on the basis of his findings the author believes that the Tawny Owl could easily be considered a trogloxene animal, i.e. a periodical visitor of the karst underground.
Keywords: bird; Birds; ptice; ornitologija; Ecosystem; sove; lesna sova